Epidermal Lamellar Body Biogenesis: Insight Into the Roles of Golgi and Lysosomes - Mahanty, Sarmistha; Setty, Subba Rao Gangi (Frontiers in Cell and Developmental Biology, 2021)
Epidermal lamellar bodies (eLBs) are secretory organelles that carry a wide variety of secretory cargo required for skin homeostasis. eLBs belong to a class of organelles called lysosome-related organelles (LROs), which are cell-type specific organelles that perform diverse functions. The formation of eLBs is thought to be related to that of other LROs, which are formed either through the gradual maturation of Golgi/endosomal precursors or by the conversion of conventional lysosomes. Current evidence suggests that eLBs biogenesis presumably initiate from trans Golgi and receive cargo from endosomes, and also acquire lysosome characteristics during maturation. These multistep biogenesis processes are frequently disrupted in human skin disorders. However, many gaps remain in our understanding of eLB biogenesis and their relationship to skin diseases. Here we describe our current understanding on eLB biogenesis with a focus on cargo transport to this LRO and highlight key areas where future research is needed.